Anatomy of Indian Bamboos Part I - Ghosh, S. S.; Negi, B. S. (Indian Forester, 1960)
Anatomical structure of epidermis of monocotyledons has often been of great practical value in identification. In the case of bamboos, epidermal studies have got special significance as floral characters are not readily available due to the flowering taking place only once in their life time. With a view to assess the diagnostic value of stem epidermis of Indian bamboos, six important species viz., Bambusa arundinacea Willd., B. Polymorpha Munro, B. vulgaris Schrad, Dendrocalamus membranaceus Munro, D. strictus Nees and Melocanna bambusoides Trin. have been investigated. The size, frequency, distribution and other characteristics of various epidermal structures useful in identification have been recorded and depicted. The exodermic epidermal appendages such as hairs and spines which commonly occur on the bamboo skin have also been studied and recorded.